Credit scoring and risk management in islamic banking: the case of Al Etihad Credit Bureau - Alhammadi, Mohamed Abdulraheem Ahmed; Ibañez-Fernandez, Alberto; Vergara-Romero, Arnaldo (Revista Venezolana de Gerencia, 2024)
This current research aims to assess the performance of Al Etihad Credit Bureau (AECB) operating in the United Arab Emirates (U.A.E.) in reducing credit risk in the Islamic banking model. The research aims to clarify the effects of credit scores on credit risk management in Islamic banks and the extent of adopting Islamic banks of these ratings when evaluating the borrowers. The study was done based on a primary qualitative research method where six top managers from AECB and nine managers from UAE’s Islamic banks who are involved with credits within the bank were interviewed using a structured interviews approach. It was found that Islamic banks perceive AECB services and products as useful for credit scoring and risk management as a supplement to their internal subjective rules and guides. AECB applies the same rating across banks and financial institutions in the UAE. The study has implications for Islamic banks, AECB, and financial policymakers in the UAE.